Synthesis method and application of Dopa / Ocs / PLGA / mof at nHA bionic bone glue
Through the synthesis of Dopa/Ocs/PLGA/mof@nHA bionic bone glue, the shortcomings of existing biological bone glue in both mechanical and biological properties are solved, and effective bone repair and immune microenvironment regulation of osteoporotic bone defects are achieved. , demonstrates excellent viscosity properties and biocompatibility.
Patent Information
- Application Number
- CN202411342807.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The existing biological bone glue has insufficient attribute mechanical properties at the structural design level, and its functional applications are mainly limited to the single level of adhesive performance or biological performance, which cannot effectively meet the treatment needs of osteoporotic bone defects.
Using the synthesis method of Dopa/Ocs/PLGA/mof@nHA bionic bone gel, multifunctional with excellent viscosity performance and bone repair ability is prepared by regulating the metabolism of aging macrophages and promoting osteogenesis, combining structural stability and biological activity. Bionic bone glue.
It has achieved structural stability and immune microenvironment regulation capabilities during bone repair in the osteoporotic bone defect area, significantly promoted the healing of osteoporotic fractures and bone defects, and demonstrated excellent degradability and biological phase. Capacity.
Smart Images

Figure CN119185625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bionic bone glue, and specifically relates to a synthesis method of Dopa / Ocs / PLGA / mof@nHA bionic bone glue and application thereof. Background Art
[0002] In recent years, the development of synthetic biological glue has opened up new avenues for the treatment of fractures and bone defects. Its bonding effect on fracture fragments not only avoids the various disadvantages brought by metal implants, but also ensures the precise anatomical alignment of the fracture site. At present, cyanoacrylate (CA) has been used in the clinical treatment of comminuted fractures. By using biological glue to splice and bond the broken bones, it can assist traditional internal fixation devices in repairing bone defects. Although CA exhibits excellent bonding properties, its biodegradability is extremely limited. The metabolites produced after degradation will not only hinder the regeneration process of bone tissue, but may even produce harmful substances during the degradation process, posing a potential threat to the organism.
[0003] Subsequently, scholars continued to explore. For example, Shanshan Hu et al. synthesized bone glue with wet adhesion function by integrating levodopa (L-DOPA) and zeolite imidazolate framework-8 nanoparticles (ZIF-8NP) with polyvinyl alcohol (PVA) polymer as a long-chain structure. Yanhua Liu et al. designed ZIF-8NP-modified catechol-chitosan (CA-CS) multifunctional bone glue (CA-CS / Z) to accelerate bone reconstruction by stabilizing the local mechanical conditions of bone defects and promoting osteogenic differentiation. However, the existing biological bone glues all show the problem of insufficient mechanical properties of their own properties at the structural design level, and their functional applications are mainly limited to the single level of adhesive properties or biological properties, and fail to take both into account, thus failing to effectively meet the treatment needs of osteoporotic bone defects. In view of this, it is urgent to develop a multifunctional bionic bone glue with a stable component structure, efficient component utilization, good adhesive properties and excellent biological activity to meet the challenges currently faced in clinical practice.
[0004] Based on this, the present invention aims to provide a synthesis method of Dopa / Ocs / PLGA / mof@nHA bionic bone glue and its application. Summary of the invention
[0005] The purpose of the present invention is to provide a synthesis method of Dopa / Ocs / PLGA / mof@nHA bionic bone glue and its application, using Dopa / Ocs / PLGA / mof@nHA bionic bone glue to regulate the metabolism of aging macrophages and promote osteogenesis, thereby meeting the clinical needs of bionic bone glue for regulating the immune microenvironment and bone integration.
[0006] The present invention provides a method for synthesizing Dopa / Ocs / PLGA / mof@nHA bionic bone glue, the steps comprising:
[0007] (1) Synthesis of Dopa / Ocs: Dopa was dissolved in deionized water and the pH was adjusted to 5.5, NHS solution and EDC solution were added to obtain a complex, OCS solution was added to the complex after stirring, and the pH was adjusted to 5.5 and stirring was continued;
[0008] (2) Synthesis of PLGA / mof@nHA microspheres: gelatin was dissolved in water to prepare an aqueous phase, PLGA was dissolved in dichloromethane to prepare an organic phase, the aqueous phase was slowly added to the organic phase, the resulting emulsion was added to the PVA solution after ultrasonication, and mof@nHA was added for mechanical stirring to solidify the microspheres and completely volatilize the organic solvent to obtain a PLGA / mof@nHA mixed solution, and the PLGA / mof@nHA microspheres were obtained after centrifugal washing and freeze-drying;
[0009] (3) Synthesis of Dopa / Ocs / PLGA / mof@nHA: Dopa / Ocs solution was mixed with freeze-dried PLGA / mof@nHA microspheres in a mass ratio of 1:(0.5-1).
[0010] Furthermore, the synthesis method of OCS includes: dissolving chitosan in a hydrochloric acid solution to prepare a chitosan solution; preparing a NaIO4 aqueous solution and adding it dropwise to the chitosan solution, stirring, dialyzing, and freeze-drying to obtain OCS.
[0011] Furthermore, the synthesis method of mof@nHA includes: preparing an NH4H2PO4 aqueous solution, adjusting the pH to 6, adding CaCl2 to mix evenly and reacting, ultrasonically dispersing, filtering, washing and removing the upper clear liquid to obtain a lower white paste solid; dissolving the prepared white paste solid in water and adjusting the pH to 8-9, adding gallic acid to ultrasonically disperse and react, filtering to obtain a precipitate, washing and ultrasonically dispersing, and centrifuging to obtain mof@nHA.
[0012] Furthermore, the centrifugation conditions in step (2) are 15000 rpm and 4°C for 10 min.
[0013] Furthermore, the NaIO4 aqueous solution is prepared by dissolving 0.625 g of NaIO4 in 10 mL of deionized water under dark conditions, and adjusting the pH of the mixed solution to 5.5.
[0014] Furthermore, the stirring is stirring in the dark for 24 hours; and the freeze-drying condition is vacuum freeze-drying at -40°C.
[0015] Furthermore, the conditions for the reaction after adding CaCl2 and mixing are to react at 180°C for 5 hours.
[0016] Furthermore, the reaction after adding gallic acid and ultrasonic dispersion is a reflux stirring reaction at 120° C. for 24 hours.
[0017] The present invention also provides the use of Dopa / Ocs / PLGA / mof@nHA bionic bone glue prepared by the synthesis method in the preparation of materials for regulating aging macrophage metabolism and bone integration.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention provides a Dopa / Ocs / PLGA / mof@nHA bionic bone glue, which draws on the structural advantages of reinforced concrete to prepare bionic bone concrete, aiming to provide physical support with stable structure, and has the ability to promote osteogenesis and regulate the complex immune microenvironment of aging macrophages, thereby promoting the bone repair process in osteoporotic bone defect areas. Starting from the organic and inorganic components of bones, the inorganic HA is combined with the organic bone glue through the bridge of MOF to achieve bionic components, so as to better match bone regeneration. At the same time, NHA (nanohydroxyapatite) can regulate macrophage metabolism and participate in immune regulation.
[0020] 2. The present invention achieves excellent viscosity performance by oxidizing chitosan and grafting it with dopamine, combining the viscosity of aldehyde groups and phenolic hydroxyl groups. First, chitosan is oxidized to improve the adhesion performance of chitosan. The rich adhesion mechanism of levodopa is fully utilized, and the oxidized chitosan and levodopa achieve the best adhesion effect through covalent bonding. Subsequently, PLGA and mof@nHA are mixed by microfluidic technology to prepare PLGA / mof@nHA composite microspheres with uniform size and rich pores. Finally, these composite microspheres are evenly mixed with oxidized chitosan-levodopa glue, and the new bionic bone glue of levodopa-oxidized chitosan / PLGA / mof@nHA is successfully synthesized.
[0021] 3. In the present invention, each group of materials was subjected to AFM and SEM respectively, and its preliminary surface morphology was first observed, and then it was magnified to 500um for further detection. After the oxidized chitosan was combined with L-DOPA, its Ra value changed significantly, and the root mean square roughness value Rq was greatly reduced, which shows that the combination of amino and carboxyl groups makes the overall surface roughness of L-DOPA-oxidized chitosan (DO) smaller, and the combination between the two is closer. After further adding PLGA and mof@nHA, the Ra and Rq values only increased slightly, indicating that the combination between the components of the bionic bone glue achieved a satisfactory effect. Fourier transform infrared spectroscopy (FTIR) and electron energy diffraction analysis (XPS) show that after the combination, the carbon and oxygen content changed significantly, which further verified that the carboxyl group and the amino group were combined through a dehydration condensation reaction. Therefore, XPS and FTIR can show that the chemical bond combination inside DOPM is very stable.
[0022] 4. The Dopa / Ocs / PLGA / mof@nHA bionic bone glue prepared by the present invention exhibits excellent operating performance, such as injectability. The experimental results show that the bionic bone glue can provide strong adhesion to ex vivo pig bone tissue, which is due to the synergistic effect of multiple adhesion mechanisms such as phenolic hydroxyl groups, aldehyde groups and levodopa. In in vitro experiments, BMSCs cells cultured with the bionic bone glue showed excellent ability to promote osteogenic differentiation, and the proportion of M2 phenotype macrophages also increased significantly. After subcutaneous implantation experiments in SD rats, the material showed excellent degradability and biocompatibility. This excellent performance is mainly due to the excellent biofriendly properties of PLGA and nHA. Finally, levodopa-oxidized chitosan was added.
[0023] / PLGA / mpf@nHA was successfully applied to the femoral condyle bone defect model of elderly female SD osteoporotic rats, further confirming the powerful ability of this new bone glue material in regulating aging macrophages and bone regeneration (II). Therefore, this new bionic bone glue has great potential in the treatment of osteoporotic fractures and bone defect healing, and provides new ideas and solutions for promoting the further development of bone glue materials in clinical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1This is a schematic diagram of the preparation process of Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue of the present invention;
[0026] Figure 2 This is the XPS analysis result;
[0027] Figure 3 Results of AFM and SEM analysis;
[0028] Figure 4 The results are from in vitro adhesion experiments;
[0029] Figure 5 It is the CCK-8 result;
[0030] Figure 6 Immunofluorescence morphology of BMSCs cells;
[0031] Figure 7 It is the fluorescence result of cell osteogenesis-related indicators;
[0032] Figure 8 is the expression of osteogenesis-related genes;
[0033] Fig. 9 The staining results of ALP and ARS;
[0034] Fig.10 It is the ALP kit detection and extracellular matrix mineralization quantitative results;
[0035] Fig.11 This is the three-dimensional reconstruction result of rat femur;
[0036] Fig.12 It is CT quantitative analysis;
[0037] Fig.13 This is the result of HE staining of femur. DETAILED DESCRIPTION
[0038] The technical scheme of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0039] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0040] Chitosan (CS; low molecular weight Mw: 50000-190000 g / mol, degree of deacetylation: 75-85%) was purchased from Sigma-Aldrich (St. Louis, MO, USA);
[0041] Levodopa (Aladdin, Shanghai, China; CAS number: 59-92-7; C9H11NO4; molecular weight: 197.19Da);
[0042] N-Hydroxysuccinimide ester (NHS; 16 mmol; CAS number: 6066-82-6; molecular weight: 115.09 Da; MedChemExpress, New Jersey, USA);
[0043] N-ethyl-N-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC, 16 mmol; CAS number: 25952-53-8; molecular weight: 191.70 Da; MedChemExpress, New Jersey, USA)
[0044] Polyvinyl alcohol (PVA, CAS No.: 9002-89-5, Mw 13,000-23,000, Aladdin, Shanghai, China)
[0045] Dichloromethane (CH2Cl2, CAS No.: 75-09-2, Mw 84.93, Merck, Aladdin, Shanghai, China)
[0046] Gallic acid ((HO)3C6H2CO2H, CAS No. 149-91-7, Mw 170.12, Merck, Darmstadt, Germany)
[0047] Example
[0048] like Figure 1 As shown in the figure, the preparation of bionic bone glue inspired by "concrete" and its application in promoting the reconstruction of osteoporotic bone defects in the elderly. First, chitosan (CS) was oxidized and modified using NaIO4 to obtain oxidized chitosan (Ocs). Then, levodopa (Dopa) was combined with Ocs and added to PLGA / mof@nHA to assemble and synthesize DOPM.
[0049] The synthesis method of Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue provided by the present invention comprises the following steps:
[0050] 1. Synthesis of OCS: 4 mmol of chitosan was dissolved in 50 mL of hydrochloric acid solution with a pH of 5.0 and stirred continuously for 24 hours to completely dissolve the chitosan; at the same time, 0.625 g of NaIO4 was dissolved in 10 mL of deionized water under dark conditions, and the pH of the mixed solution was adjusted to 5.5; the NaIO4 solution was added dropwise to the chitosan solution and stirred in the dark for 24 hours; the oxidation of chitosan would convert its abundant hydroxyl groups into aldehyde groups (CHO groups); subsequently, the solution was dialyzed using a polymer filter membrane (1k Da dialysis bag) for 24 hours, wherein the dialysis solvent (deionized water) was replaced every 8 hours; the dialyzed product was subjected to vacuum freeze-drying at -40°C to finally obtain freeze-dried OCS.
[0051] 2. Synthesis of Dopa / Ocs:
[0052] Dopa (8 mmol) was dissolved in 100 mL of deionized water and the pH was adjusted to 5.5 by adding HCl; 2 mL of 50 mM NHS aqueous solution was added to the Dopa solution and stirred for 15 minutes; then 2 mL of 50 mM EDC aqueous solution was added to the reaction mixture and stirred for 15 minutes to reach the final reaction complex; finally, 4 mmol of lyophilized Ocs synthesized in step 1 was added to the reaction mixture and its pH was adjusted to 5.5 by adding NaOH and stirring was continued for 24 hours.
[0053] 3. Synthesis of nHA: Weigh 4.2516g NH4H2PO4 into a 50mL beaker, add 35mL deionized water, add 3mol / L HNO3 solution to adjust pH=6, continue to weigh 4.4320g CaCl2 and add it to the above NH4H2PO4 solution, stir and mix, adjust pH=5, prepare a mixed solution, stir vigorously to mix it evenly, transfer it to a reactor, place it in an electric constant temperature blast drying oven, react it at 180°C for 5h, then take out the reactor and cool it to room temperature, ultrasonicate for 10min to disperse it evenly, centrifuge and filter it with a centrifuge tube, wash it three times with water and remove the upper clear liquid to obtain the lower white paste nHA solid.
[0054] 4. Synthesis of mof@nHA: Weigh 5.65 g of nHA into 25 mL of water, adjust the pH to 8-9, and disperse it evenly by ultrasonication; add 0.3 g of gallic acid, disperse it evenly by ultrasonication for 10 min, place it in a three-necked flask and reflux with stirring, react at 120°C for 24 h, cool to room temperature, filter the precipitate, wash it three times with deionized water and anhydrous ethanol respectively, disperse it ultrasonically, and recover it by high-speed centrifugation to obtain mof with nano-hydroxyapatite as the core, namely mof@nHA.
[0055] 5. Synthetic PLGA / mof@nHA: PLGA was synthesized using microfluidic technology, and customized coaxial needles (25G, 18G), internal metal channels (inner diameter 0.26mm×outer diameter 0.51mm) and external metal channels (inner diameter 0.84mm×outer diameter 1.27mm) were connected by polyvinyl chloride (PVC) tube connectors.
[0056] First, 0.75 g of gelatin was dissolved in 10 mL of deionized water to prepare an aqueous phase, and then 0.2 g of PLGA was dissolved in 10 mL of dichloromethane to prepare a PLGA solution as an organic phase; then 2 g of the gelatin aqueous phase was slowly injected into the 6 g of PLGA solution using a syringe, and ultrasonically treated for 5 minutes (within 5 minutes, 5 seconds as a cycle, ultrasonic oscillation for the first 3 seconds, and rest for the last two seconds), and passed through the inner channel as a discontinuous phase; polyvinyl alcohol (PVA) solution passed through the outer channel as a continuous phase; the flow rate ratio of the two phases was fixed at 1:18. Next, the obtained emulsion was poured into 1000 mL of 0.75% PVA aqueous solution, and the mof@nHA in step 4 was added and stirred at room temperature to solidify the microspheres and completely evaporate the organic solvent to obtain a PLGA / mof@nHA mixed solution; after centrifugation at 15000 rpm and 4°C for 10 min, the supernatant was discarded, resuspended and rinsed repeatedly three times with PBS, and freeze-dried at -80°C for 48 h to obtain PLGA / mof@nHA microspheres, which were sealed and stored in a 4°C refrigerator; the finally collected PLGA / mof@nHA microspheres were freeze-dried at -80°C for 1 day.
[0057] 6. Synthesis of Dopa / Ocs / PLGA / mof@nHA: The Dopa / Ocs solution was mixed with the freeze-dried PLGA / mof@nHA microsphere carrier in a mass ratio of 1:0.75 to obtain the final product.
[0058] Test Example 1: Characterization
[0059] FTIR was performed using a Fourier transform infrared spectrometer (PerkinElmer, USA). The topological morphology of the material surface was observed by SEM (Hitachi S-4800, Japan) at 12 kV. The rheological behavior of bone glue was characterized using a rheometer (AntonPaarMCR 302, Austria). Mechanical properties were tested using a mechanical testing machine (Hengyi, Shanghai, China).
[0060] XPS was used to detect and analyze the chemical composition of the sample surface. In the XPS spectrum, the carbon and oxygen contents underwent clear changes after the reaction, which further verified that the carboxyl group and the amino group were combined through a dehydration condensation reaction.
[0061] Figure 1The total peak graph shows that the changes in elements such as C, N, and O are specifically reflected. After comparing the peak values of O content before and after the combination of Dopa and Ocs, the results show that the content of O has decreased to a certain extent in the DO group, while the peak value of C content has increased to a certain extent. This shows that after the combination of the two, the carbon and oxygen contents have undergone clear changes, which further verifies that the carboxyl group and the amino group are combined through a dehydration condensation reaction. In summary, XPS and FTIR show that the chemical bonds within DOPM are very stable.
[0062] Each group of materials was subjected to AFM (atomic force microscopy) and SEM (scanning electron microscopy) to obtain Figure 2 First, its preliminary surface morphology was observed, and then it was magnified to 500um for further detection. The AFM test was used to test the change process of the roughness of the reaction material surface. L-DOPA was used as a bone glue precursor, and its AFM measured Rq and Ra values were 1.27nm and 0.993nm, respectively, and the Roughness reached 10.8nm, while the Rq and Ra values of oxidized chitosan were 5.12 and 3.74nm, respectively, and the Roughness value reached 78.6nm. The mean square value change of the test results of each group can be intuitively observed that after the oxidized chitosan was combined with L-DOPA, its Ra value changed significantly, and the root mean square roughness value Rq was greatly reduced, which shows that the combination of amino and carboxyl groups makes the overall surface roughness of L-DOPA-oxidized chitosan (DO) smaller, and the combination between the two is closer. After further addition of PLGA and mof@nHA, the Ra and Rq values increased only slightly. Compared with the L-DOPA-oxidized chitosan / PLGA (DOP) group, the Ra value of the DOPM group increased by 3% and the Rq value increased by 16%, indicating that the combination of the components of the bionic bone glue achieved a satisfactory effect. In order to better observe the morphological characterization of each group of materials and the morphological changes after combination, we used SEM to detect the materials. The image shows that the pore size (120um+14um) on the surface of oxidized chitosan (Ocs) is very uniform and dense, which is conducive to its adhesion to the bone surface and provides a good basic condition for bone healing. Similarly, after the combination of L-DOPA and oxidized chitosan, the surface characteristics of DO combined the advantages of both. After the addition of PLGA microspheres, the resulting DOP surface was rich in a large number of microspheres. After scanning mof@nHA alone, it can be observed that a large number of nano-hydroxyapatite are combined with its typical hexagonal model structure. Finally, the DOPM group can more intuitively observe that the components are tightly combined like a concrete structure. The excellent structure is a prerequisite for the new bionic bone glue to exert its function.
[0063] Experimental Example 2: Cell Culture
[0064] Rat bone marrow mesenchymal stem cells (BMSCs) were isolated and cultured from the bone marrow of 4-week-old female SD rats using a method approved by the Ethics Committee of the First Affiliated Hospital of the University of Science and Technology of China. Specifically, the femur of the rat was isolated under sterile conditions, and both ends of the femur were gently cut off using ophthalmic scissors. PBS was drawn with a 5 mL sterile syringe to repeatedly rinse the femoral bone marrow cavity until it turned white, and the bone marrow fluid was collected and filtered using a 40 um cell sieve. The filtered bone marrow fluid was collected and centrifuged in a centrifuge and centrifuged at 1500 rpm for 10 minutes. The extracted BMSCs were cultured in α-DMEM medium (Dulbecco's modified Eagle medium, Gibico, USA) containing 10% FBS (fetal bovine serum, Gibico, USA), 100 U mL-1 penicillin G and 0.1 mg mL-1 streptomycin (Gibico, USA) at 37°C, 5% CO2, and saturated humidity in a cell culture incubator. When cultured to the third generation, BMSCs cells were identified by flow cytometry using CD44, CD73, CD45, CD11b and CD105 antibodies (1:100, Abcam, USA). Results: CD44, CD73, CD105 were positive (>90%) and CD45, CD11b were negative (<5%), indicating that the isolated cells were BMSCs cells and could be used for cell experiments.
[0065] Test Example 3: Cytocompatibility
[0066] The cell biocompatibility of bone glue was evaluated by CCK-8 method (Solarbio, China). RAW264.7 cells and BMSCs cells in logarithmic growth phase were prepared into cell suspensions, and the cells were counted under a microscope at 4×10 3The cells were seeded in a 96-well plate at a density of 2 × 104 cells / well and placed in an incubator for culture. After the cells adhered to the wall, the extract was added and cultured for 1 day, 3 days and 7 days respectively. After the above treatment steps were completed, 100 μL of CCK-8 solution was added to the 96-well plate and placed in a 37°C incubator for incubation for 2 hours. The 96-well plate was then placed in a microplate reader (BIO-TEK; USA), and the optical density (OD) value at a wavelength of 450 nm was measured, and the cell activity was calculated based on this. The specific formula is as follows: Cell viability = (OD s caffold-OD Blank) / (ODcontrol-OD Blank) × 100% In this formula, OD s caffold is the OD value of the experimental group, OD control is the OD value of the control group, and OD Blank is the OD value of the blank group. Then RAW264.7 cells and BMSCs cells were seeded in a 24-well plate at a density of 2 × 104 cells / well, and the extract was added and cultured for 3 days. Then, live / dead cells were evaluated using a fluorescent live / dead cell double staining kit (Beyotime, China). 5 μL of calcein (AM) and 15 μL of propidium iodide (PI) were dissolved in 5 mL of PBS to prepare the staining solution. After adding the staining solution, incubate for 30 minutes, and observe and record the fluorescent staining images of live / dead cells at wavelengths of 490 nm and 535 nm using an inverted fluorescence microscope.
[0067] Experimental Example 4: Immunofluorescence staining
[0068] BMSCs cultured on different samples were determined by fluorescence staining. In brief, the cells were intervened accordingly according to the experimental requirements, washed 2-3 times with PBS, fixed with 4% paraformaldehyde for 10 min, discarded paraformaldehyde and washed with PBS, permeabilized with 0.1% Triton X-100 (Beyotime, China) and blocked with immunostaining blocking solution (Beyotime; China). Then, the primary antibody of the target molecule was added to the cells and incubated overnight at 4°C. Then, the cells were incubated with the fluorescently labeled secondary antibody of the corresponding species at room temperature in the dark for 1 hour. The cell nuclei were stained by using phalloidin (Yeasen, China), and finally the slides were sealed with antifade mounting medium. The fluorescently labeled cells were captured using a laser confocal microscope (Zeiss, Germany) in a dark environment. The intensity of the fluorescence of the target protein was evaluated using Image J (Bethesda, USA).
[0069] Experimental Example 5: In vitro osteogenic differentiation
[0070] All grouping materials were sterilized by Co-60 irradiation. The materials were placed in the upper chamber of the Transwell device (Corning, American), and 1.0×104 bone marrow mesenchymal stem cells were cultured in the lower chamber. When the cell density was 60%, the cell culture medium was replaced with osteogenic induction medium, and the culture medium was changed every 3 days. After 7 days of culture, PBS was washed 1-2 times and fixed with 4% paraformaldehyde. Then, the samples were stained with an alkaline phosphatase (ALP) staining kit (Beyotime, China) according to the instructions. Cell morphology was observed under an optical microscope. To quantify ALP activity, after 7 days of culture, the culture medium was discarded and the cells were incubated with 0.1% TritonX-100 for 1 minute. After centrifugation, ALP activity was detected using an AKP / ALP kit (Beyotime, China). After 21 days of culture, BMSCs were fixed with 4% paraformaldehyde and stained with an Alizarin Red staining kit (Cyagen, China) according to the instructions. The cells were then observed under a microscope. To determine the amount of calcium deposits, 1 mL of 10% cetylpyridinium chloride was added to each well after staining to dissolve the stained calcium nodules. After 1 hour, the absorbance was measured at 562 nm by a microplate reader.
[0071] Experimental Example 6: Western blotting experiment
[0072] RAW264.7 cells and BMSCs cells were plated and treated according to the experimental purpose. The culture plates were then placed on ice and rinsed three times with pre-cooled PBS. The total protein was extracted from the cells by adding protease inhibitors and RIPA lysis buffer. The protein concentration was determined using the BCA protein concentration detection kit according to the operating manual. The concentration of each protein was adjusted with 5× protein loading buffer, boiled in a boiling water bath for 5 minutes, and then stored in a -20°C refrigerator. The proteins were separated by SDS-PAGE gel electrophoresis (FUDE BIOLOGICAL, China). After the electrophoresis, they were transferred to PVDF membranes using wet transfer. After the transfer, the PVDF membrane was placed in an incubation box containing TBST and blocked with 5% skim milk at room temperature for 1 hour on a shaker. After the blocking was completed, the membrane was washed three times with TBST. Subsequently, the primary antibody was diluted according to the instruction manual and added to the incubation box and incubated with the PVDF membrane at 4°C on a shaker overnight. After the primary antibody incubation, the primary antibody was recovered and TBST was added to wash the membrane 3 times on a shaker for 5 minutes each time. The secondary antibody was diluted at a ratio of 1:5000 and added to the incubation box to completely cover the PVDF membrane and incubate at room temperature for 2 hours. After washing the membrane 3 times with TBST, excess water was removed with absorbent paper, and the membrane was placed in a light-proof box containing ECL chemiluminescent solution for full reaction for 2 minutes. The chemiluminescent gel imaging system (Proteinsimple, USA) was used for exposure, and the results were analyzed using AlphaEaseFC software to analyze the grayscale value of the protein bands.
[0073] Experimental Example 7: Macrophage Transcriptome Sequencing
[0074] Macrophages were intervened with LPS (10 ng / mL) and bone gelatin extract, respectively. After 24 hours of incubation, total cellular RNA was extracted using Trizol (ThermoScientific, USA) and frozen at -80°C. RNA purity and quantification were identified using a NanoDrop2000 spectrophotometer (ThermoScientific, USA), and RNA integrity was assessed using an Agilent2100Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA). The library was sequenced using the IlluminaNovaseq6000 sequencing platform, and 150 bp double-end reads were generated. Fastp software was used to obtain cleanreads for subsequent data analysis. Gene expression (FPKM) was calculated using HISAT2 software, and sample biological repeats were evaluated using HTSeq-count and R (v3.2.0). Differentially expressed genes were analyzed using DESeq2 software, and genes that met the thresholds of q value < 0.05 and foldchange > 2 or foldchange < 0.5 were defined as differentially expressed genes (DEGs). DEGs were analyzed using R (v3.2.0) to display the expression patterns of genes in different groups and samples. Subsequently, GO, KEGG, Pathway, Reactome, and WikiPathways enrichment analysis was performed on differentially expressed genes based on the hypergeometric distribution algorithm to screen significant enrichment function entries. R (v3.2.0) was used to draw bar charts, chord charts, or enrichment analysis circle charts for significant enrichment function entries. GSEA software was used for gene set enrichment analysis. Using predefined gene sets, genes were ranked according to the degree of differential expression in the two types of samples, and then the pre-defined gene sets were tested to see whether they were enriched at the top or bottom of this ranking table.
[0075] Experimental Example 8: qRT-PCR
[0076] Cell culture was the same as the above experiment, and the expression of target mRNA in cells was detected by qRT-PCR. The specific steps are as follows: Total RNA was extracted using SimplyP Total RNA Extraction Kit (EZBioscience; USA) according to the reagent instructions, and the RNA concentration was determined by Nanodrop 2000 (Thermo; US), and then reverse transcribed and synthesized into cDNA using HiScript III-RT SuperMix for qPCR Kit. qRT-PCR detection was performed according to the instructions of ChamQ Universal SYBRqPCR MasterMix Kit. The relative gene expression was calculated using the 2-ΔΔCt method, and the expression level of the relevant gene was based on GAPDH.
[0077] ALP forward: 5'-GGGGTCAAAGCCAACTACAA-3',
[0078] ALP reverse: 5′-CTTCCCTGCTTTCTTTGCAC-3′;
[0079] Runx2 forward: 5'-GCCGGGAATGATGAGAACTA-3',
[0080] Runx2 reverse: 5′GGACCGTCCACTGTCACTTT-3′;
[0081] COL1A1 forward: 5'-AATGGTGCTCCTGGTATTGC-3',
[0082] COL1A1 reverse: 5′-GGTTCACCACTGTTGCCTTT-3′;
[0083] OCN forward: 5'-GAGGGCAGTAAGGTGGTGAA-3',
[0084] OCN reverse: 5′-GTCCGCTAGCTCGTCACAAT-3′;
[0085] GAPDH forward: 5'-TGACCTCAACTACATGGTCTACA-3',
[0086] GAPDH reverse: 5′-CTTCCCATTCTCGGCCTTGTACA-3′.
[0087] Experimental Example 9: In vivo modeling
[0088] SD rats (female, 2 months old, weighing 200 ± 20 g) and SD rats (female, 16 months old, weighing 450 ± 100 g) were purchased from the Animal Experiment Center of the First Affiliated Hospital of University of Science and Technology of China. All experimental procedures were approved by the Ethics Committee of the First Affiliated Hospital of University of Science and Technology of China (NO.202404141422000111849). Micro-CT showed that the osteoporosis model was successfully established, and then bone defect surgery was performed. The lateral femoral condyle was exposed after the skin was cut layer by layer. A defect with a diameter of 5 mm and a depth of 5 mm was made on the lateral femoral condyle with an electric drill, and the materials of each group were added to the bone defect. The rats were euthanized in batches at 2 weeks, 4 weeks, and 8 weeks, and the intact femoral specimens were removed and fixed with 4% paraformaldehyde for further analysis.
[0089] Test Example 10: Osseointegration Assessment
[0090] The specimens were examined by micro-computed tomography (micro-CT). The micro-CT scanning parameters were set as follows: working voltage 80KV, current 385μA, exposure time 240ms, and scanning thickness 18μm. After scanning, 3-D Creator software was used to reconstruct the three-dimensional image using the Feldkamp algorithm. After image reconstruction, the region of interest (ROI) was manually selected layer by layer within the femoral condylar defect, and the three-dimensional image was reconstructed. CTvox was used to analyze the bone volume / tissue volume (BV / TV), trabecular width (Th.Th), trabecular number (Tb.Th), and bone volume / tissue volume (BV / TV). Bone volume / tissue volume (BV / TV), trabecular width (Th.Th), trabecular number (Tb.N), and bone mineral density (BMD) were used to analyze the treatment effect of osteoporotic bone defects. A digital slice scanner (KF-PRO-120, KFBIO) was used to acquire panoramic images of the entire slice. Femoral specimens were decalcified with 10% ethylenediaminetetraacetic acid (SigmaAldrich) for 1 month after CT scanning, and then embedded in paraffin and sliced using a SP1600 saw slicer produced by Leica Biosystems, Germany. All sections were stained with HE, Masson staining, and immunohistochemistry. Primary antibodies and corresponding HRP-labeled secondary antibodies were incubated for immunohistochemistry (IHC) staining.
[0091] Test Example 11: Statistical Analysis
[0092] All quantitative data are expressed as mean ± standard deviation. Data were analyzed using GraphPadPrism 9.2 software. The Kolmogorov Smirnov method was used to analyze the normality of the data, followed by one-way analysis of variance (ANOVA) and t-test. Tukey's post hoc method was used to determine individual differences between groups. *: p < 0.05; **: p < 0.01; ***: p < 0.001; ****: p < 0.0001.
[0093] In vitro results:
[0094] Cell proliferation experiment (CCK-8) showed that after modification, the cell proliferation was significantly increased compared with the control group. Vinculin immunofluorescence images showed that the BMSCs cells in the DOPM group spread more fully and had stronger fluorescence intensity, while the cells in the Control group had obvious shrinkage.
[0095] RT-PCR results showed that DOPM can effectively promote ALP, COL1A1 and OCN (osteoblast differentiation markers), Runx2 (the main transcription factor for osteoblast differentiation). ALP staining and ARS staining can be observed that the darkest staining color is in the DOPM group ( Figure 3-10 ).
[0096] in, Figure 3 In vitro pig bone adhesion experiment: Various in vitro adhesion experiments were carried out to demonstrate the potential of bone glue in real-world applications. The femoral head of the ex vivo pig bone was sawed off, and bone glue was evenly applied to the broken ends. After the broken ends were re-joined, the fracture was effectively fixed and then soaked in a 37°C PBS solution overnight. After the femoral head was punched and threaded, it could easily lift a 10kg weight.
[0097] Figure 4 For the CCK-8 experiment, in order to study the effect of the material on BMSCs cell proliferation, RAW264.7 cells were cultured for 1, 3, and 7 days, and the OD values were collected using a cell counting kit (CCK-8) under a microplate reader to indirectly confirm that RAW264.7 cells had a higher proliferation activity in the experimental group.
[0098] Figure 5The BMSCs cell Vinculin immunofluorescence staining experiment was performed. The affinity of the material to BMSCs is crucial for promoting the healing function of bone defects. After BMSCs were cultured in each group of materials for 7 days, the expression of adhesion focal protein (Vinculin), cell morphology and spreading area were observed using a laser confocal microscope. The results showed that the BMSCs in the Control group had short and thin filopodia, the cells were relatively dispersed, and the protein fluorescence intensity was weak; on the contrary, the cells co-cultured with DOPM had a full morphology and aggregated distribution, and the Vinculin fluorescence expression intensity was significantly higher than that of the other groups.
[0099] Figure 6 In order to more intuitively illustrate the in vitro osteogenic activity of bone glue, immunofluorescence staining was used to mark RUNX2 and OCN, respectively. The results showed that the fluorescence expression of BMSCs cells treated with DOPM group was higher than that of DOP group, and only very weak fluorescence was observed in the Control group.
[0100] Figure 7 For the RT-PCR experiment, the osteogenic activity of bone glue was further evaluated at the gene level by reverse transcription polymerase chain reaction (RT-PCR). Representative osteogenic-related genes, namely ALP, OCN, RUNX2, and Osterix, were studied. The mRNA expression levels of related genes in cells treated with DOPM were significantly increased.
[0101] Figure 8 For the ALP and ARS staining experiment, in order to study the effect of bone glue on promoting osteogenic differentiation of BMSCs cells in vitro, RAW264.7 cells were treated with LPS and Dopa, Ocs, DO, DOP, and DOPM, respectively. The control group used PBS as a control, and the supernatant was collected as a conditioned medium, which was indirectly co-cultured with BMSCs cells. Alkaline phosphatase staining was performed 7 days later. The staining was darker in the DO, DOP, and DOPM groups, and lighter in the Control, Dopa, and Ocs groups. Under the microscope, the cell outlines of each group were clear, the cells in the DOPM group were densely colored, and the staining of the other groups was sparse. On the 21st day, a large number of red mineralized calcium nodules appeared in the DOPM group. The results of ALP and ARS staining verified that the new bionic bone glue could induce BMSCs cells to differentiate into osteoblasts in vitro and regulate the mineralization of bone matrix.
[0102] Fig. 9 For the quantitative analysis of ALP and ARS staining experiments, the alkaline phosphatase activity kit was used to quantify the ALP activity of each group. The results showed that the ALP activity of the DOPM group was the highest. The quantitative analysis of Alizarin red staining in the DOP and DOPM groups was significantly higher than that in the Control, Dopa and Ocs groups.
[0103] Fig.10 For micro-CT analysis, in order to evaluate the healing effect of different material groups on bone defects, the materials were implanted into the bone defects according to the group arrangement. The Control group was implanted with PBS, and the femur was taken out for micro-CT three-dimensional reconstruction analysis to further evaluate the repair of the bone defect. The figure is a three-dimensional reconstruction image of the bone defect at 2 weeks, showing the excellent bone repair ability of DOPM after implantation.
[0104] Fig.11 Micro-CT quantitative analysis showed that the bone analysis parameters were the highest in the group implanted with DOPM, thanks to the combination of PLGA microspheres and nHA, which achieved better osteoconductivity and osteoinductivity. At week 8, the bone tissue density (BMD), bone volume / group volume (BV / TV) and trabecular number (Tb.N) in the DOPM group were 262%, 289% and 418% of those in the Control group, respectively. This indicates that the bone defect repair effect in aging osteoporosis rats after implantation of DOPM new bionic bone glue is the best.
[0105] Fig.12 H&E staining of bone defects. In order to more fully display the details and characteristics of bone defect healing, the samples at 2, 4 and 8 weeks were subjected to histological staining. H&E staining of femoral condyle bone defects after different treatments can be used to distinguish general bone tissue structure and cells. The figure shows the bone defect staining at 2 weeks. It can be observed that the amount of new bone formation in the Control group at different times was lower than that in the other groups at the same stage, and the bone mass in the bone defects of the experimental group after the same intervention time was higher than that of other groups.
[0106] In vitro macrophage experiments showed that compared with the Control group, the DOPM group significantly promoted the polarization of macrophages to the M2 type. The M1 phenotype marker nitric oxide synthase (iNOS) and the M2 ideal phenotype indicator arginase 1 (Arg-1) were marked by immunofluorescence staining. The fluorescence intensity of iNOS in the control group inoculated with LPS was significantly higher than that of the other groups. The fluorescence intensity of INOS in the DOPM group was the weakest compared with the other five groups. At the same time, the fluorescence intensity of Arg-1 marked in the DOPM group was significantly increased. Overall, the new bionic bone glue developed showed significant immunomodulatory effects in in vitro cell culture. Therefore, the bone glue can effectively promote the polarization of aging macrophages to the M2 type, thereby exerting an anti-inflammatory effect. In addition, it also reduces the secretion of pro-inflammatory factors and enhances the production of anti-inflammatory molecules. This combined effect effectively reverses the local persistent low-grade inflammatory response.
[0107] In vivo results:
[0108] Micro-CT examination results showed that the newly formed bone around DOPM implants was much denser than that observed in other groups. Quantitative analysis of bone mineral density (BMD), connection density (Conn.D), bone volume / total volume (BV / TV), bone surface / bone volume (BS / BV), and some other parameters such as trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) all indicated that AMP-modified implants were more conducive to bone regeneration around implants than other implants. HE staining results: A fibrous layer was formed around DO and DOP implants. In contrast, DOPM implants introduced more and denser trabecular bone because the decorated mof@nHA suppressed most of the implant inflammatory factors that hinder osteogenesis.
[0109] Anti-inflammatory experiments showed that immunohistochemical staining showed that there were a large number of M1 macrophages in the Control, Dopa and Ocs groups. At the same time, there were many inflammatory factors TNF-a distributed around the implants in these groups. However, the macrophage phenotype in the DOPM implant group was mainly M2, and TNF-a was significantly inhibited.
[0110] The in vitro cell experiments of the present invention prove that Dopa / Ocs / PLGA / mof@nHA can promote the adhesion, proliferation, and osteogenic differentiation of BMSCs, and regulate the metabolism of aging macrophages; in vivo experiments were applied to the femoral condyle bone defect model of elderly female SD osteoporotic rats, further confirming the powerful ability of this new type of bone glue material in regulating aging macrophages and bone regeneration. The results of in vivo and in vitro experiments show that the material has good biocompatibility, can effectively induce bone marrow mesenchymal stem cells to differentiate into osteoblasts, and regulate the immune microenvironment by rebuilding the homeostasis of aging macrophages, ultimately accelerating the repair and regeneration of bone tissue. In summary, the research on this bionic bone glue has brought new possibilities to the field of bone tissue engineering, has great potential in the treatment of osteoporotic fractures and bone defect healing, and provides new ideas and solutions for promoting the further development of bone glue materials in clinical applications.
[0111] The English explanations involved in the present invention are as follows:
[0112] Control: control group, Dopa: levodopa, Ocs: oxidized chitosan, DO: levodopa / oxidized chitosan, DOP: levodopa / oxidized chitosan / poly(lactic-co-glycolic acid) copolymer, DOPM: levodopa / oxidized chitosan / poly(lactic-co-glycolicacid) copolymer / metal organic framework@nanohydroxyapatite
[0113] PLGA: polylactic acid-co-glycolic acid, mof: metal organic frame, nHAorHA (NanoHydroxyapatite): nanohydroxyapatite, CS (Chitosan), OCS (Oxidized Chitosan): oxidized chitosan, EDC (N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide) / NHS (N-hydroxysuccinimide): N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide / N-hydroxysuccinimide, macrophage: macrophage, aging macrophage: aging macrophage, interaction: chemical bond,
[0114] intensity(au): intensity, Binding Energy: binding energy, Fracture: fracture, Application: application, Adhesion: adhesion, 37℃ PBS Precondition: 37 degree PBS liquid pretreatment, Force: force, OD value: absorbance, mRNA relative expression, activity: activity.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue, characterized in that the steps include: (1) Synthesis of Dopa / Ocs: Dopa was dissolved in deionized water and the pH was adjusted to 5.5, NHS solution and EDC solution were added to obtain a complex, OCS was added to the complex after stirring, and the pH was adjusted to 5.5 and stirring was continued; (2) Synthesis of PLGA / mof@nHA microspheres: gelatin was dissolved in water to prepare an aqueous phase, PLGA was dissolved in dichloromethane to prepare an organic phase, the aqueous phase was slowly added to the organic phase, the resulting emulsion was added to the PVA solution after ultrasonication, and mof@nHA was added for mechanical stirring to solidify the microspheres and completely volatilize the organic solvent to obtain a PLGA / mof@nHA mixed solution, and the PLGA / mof@nHA microspheres were obtained after centrifugal washing and freeze-drying; (3) Synthesis of Dopa / Ocs / PLGA / mof@nHA: Dopa / Ocs solution was mixed with freeze-dried PLGA / mof@nHA microspheres in a mass ratio of 1:(0.5-1).
2. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 1, characterized in that: The OCS synthesis method comprises: dissolving chitosan in a hydrochloric acid solution to prepare a chitosan solution; preparing a NaIO4 aqueous solution and dropping it into the chitosan solution, stirring, dialyzing, and freeze-drying to obtain the OCS.
3. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 1, characterized in that: The synthesis method of mof@nHA comprises: preparing an NH4H2PO4 aqueous solution, adjusting the pH to 6, adding CaCl2 to mix evenly and reacting, ultrasonically dispersing, filtering, washing and removing the upper clear liquid to obtain a lower white paste solid; dissolving the prepared white paste solid in water and adjusting the pH to 8-9, adding gallic acid to ultrasonically disperse and react, filtering to obtain a precipitate, washing and ultrasonically dispersing, and centrifuging to obtain mof@nHA.
4. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 1, characterized in that: The centrifugation conditions in step (2) are 15000 rpm and 4° C. for 10 min.
5. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 2, characterized in that: The NaIO4 aqueous solution was prepared by dissolving 0.625 g of NaIO4 in 10 mL of deionized water in the dark, and adjusting the pH of the mixed solution to 5.
5.
6. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 2, characterized in that: The stirring is carried out in the dark for 24 hours; and the freeze-drying condition is vacuum freeze-drying at -40°C.
7. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 3, characterized in that: The conditions for the reaction after adding CaCl2 and mixing are to react at 180°C for 5 hours.
8. The method for synthesizing Dopa / Ocs / PLGA / mof@nHA biomimetic bone glue according to claim 3, characterized in that: After adding gallic acid and ultrasonic dispersion, the reaction is reflux stirring reaction at 120° C. for 24 hours.
9. Use of Dopa / Ocs / PLGA / mof@nHA bionic bone glue prepared by the synthesis method according to any one of claims 1 to 8 in the preparation of materials for regulating aging macrophage metabolism and bone integration.
